Модели для создания информационных технологий по выполнению функций и задач управления импульсной многоплановой защитой - Кряжич, О.А. (Екологічна безпека та природокористування, 2012)
In work the analysis of typical features and system requirements of the chemical enterprise is carried out. The enterprise as object of protection against occurrence of technogenic failure is considered. Processes occurring at the enterprise are investigated. It is made for the purpose of formation of certain criteria of conformity. On the basis of criteria on which basis functional models of increase of safety of the chemical enterprise are offered. Information models and algorithms of formation of a control system on the basis of pulse protection frames from explosion and a fire are offered by pulse multiplane protection of the chemical enterprise.